Scoping review of biological treatment of deficiency of interleukin-36 receptor antagonist (DITRA) in children and adolescents - Toni Hospach; Fabian Glowatzki; Friederike Blankenburg; Dennis Conzelmann; Christian Stirnkorb; Chris Sandra Müllerschön; Peter von den Driesch; Lisa Maria Köhler; Meino Rohlfs; Christoph Klein; Fabian Hauck (BMC, 2019)
Abstract Background Deficiency of interleukin-36 receptor antagonist (DITRA) is a life threatening monogenic autoinflammatory disease caused by loss of function mutations in the IL36RN gene. Affected patients develop recurrent episodes of generalized pustular psoriasis (GPP) with systemic inflammation and fever. We here review and analyze the literature on pediatric DITRA patients who have been treated by biologicals targeting inflammatory cytokines. Method A database research was performed to identify all relevant articles on pediatric DITRA patients treated with biologicals. According to defined response criteria therapeutic efficacy was analyzed. Results Our literature research revealed 12 pediatric patients with DITRA who have received treatment with biologicals and we add a further not yet reported patient. Out of these 13 patients 10 were homozygous including 6 with the p.Leu27Pro, 3 with the p.Arg10 Argfs* and 1 with the p.Thr123Met mutation. 3 patients were compound heterozygous. In total 28 flares were treated with biological agents- targeting IL-1, IL-17, IL-12/23 and TNF-α. Complete response was achieved in 16 flares (57%), a partial reponse was seen in 2 flares (7%), and no response was observed in 10 flares (36%). Response rates were heterogeneous among the different agents. While complete/partial/no response with inhibition of TNF-alpha could be achieved in 7 (58%)/1 (8%)/4 (33%), the inhibition of IL-17 and of IL-12/23 led in each 4 flares to a 100% complete response. IL-1 inhibition led to complete/partial response in each 1 (13%) and was not effective in 6 (76%) flares. Of note, the novel patient was successfully treated with weekly dosed adalimumab. Conclusions DITRA is a rare disease that has to be considered in GPP with systemic inflammation and fever. It can be effectively treated with specific biological inhibition of TNF-alpha, IL-12/23 and IL- 17, while anti-IL-1 treatment seems less effective. Weekly dosed adalimumab appears to be a treatment option for pediatric patients. Further reports and studies of biological treated pediatric DITRA patients are warranted for evaluation of optimal treatment.